Functional tricuspid stenosis: a rare presentation of suspected rhabdomyoma as congenital cyanotic heart disease. (12th January 2017) - Nair, Anishkumar; Rajesh, Gopalan Nair; Sajeev, Chakanalil Govindan
Abstract: Cardiac tumours in newborns are often asymptomatic and can be sporadically detected on routine screening unless they result in intractable arrhythmias or haemodynamically significant obstructions causing heart failure. Their presentation as a cause of congenital cyanosis is never anticipated. We report a rare case of a newborn presenting with congenital cyanosis consequent to suspected cardiac rhabdomyoma causing tricuspid inflow obstruction. Our experience with this patient with two large cardiac masses illustrates the significance of its inclusion in the differential diagnosis of perinatal cyanosis, as early detection and surgical management might be the only lifesaving options, if performed well in time.